1986
DOI: 10.1007/bf00500007
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a selective 5-HT reuptake blocker, citalopram, on the sensitivity of 5-HT autoreceptors: Electrophysiological studies in the rat brain

Abstract: Citalopram (CIT), is a selective serotonin (5-HT) reuptake blocker and a clinically effective antidepressant. The present electrophysiological studies were undertaken to investigate in vivo the acute and long-term effects of CIT administration on 5-HT neurotransmission. In a first series of experiments, a single dose of CIT (0.05-0.5 mg/kg) was administered intravenously to naive rats while recording the activity of a 5-HT-containing neuron in the nucleus raphe dorsalis. A dose-response relationship of the inh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

18
164
0

Year Published

1989
1989
2000
2000

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 298 publications
(182 citation statements)
references
References 39 publications
18
164
0
Order By: Relevance
“…The acute intravenous administration of 5-HT reuptake inhibitors suppresses the firing activity of the 5-HT neurons of the dorsal and median raphe nuclei (de Montigny et al 1981;Blier et al 1984;Chaput et al 1986;Hajós et al 1995) ACh-induced firing activity in control and in 5,7-DHT-lesioned rats is shown in B. * p Ͻ .01, compared to control values using the non-paired Student's t-test.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The acute intravenous administration of 5-HT reuptake inhibitors suppresses the firing activity of the 5-HT neurons of the dorsal and median raphe nuclei (de Montigny et al 1981;Blier et al 1984;Chaput et al 1986;Hajós et al 1995) ACh-induced firing activity in control and in 5,7-DHT-lesioned rats is shown in B. * p Ͻ .01, compared to control values using the non-paired Student's t-test.…”
Section: Discussionmentioning
confidence: 99%
“…The acute intravenous administration of 5-HT reuptake inhibitors suppresses the firing activity of the 5-HT neurons of the dorsal and median raphe nuclei (de Montigny et al 1981;Blier et al 1984;Chaput et al 1986;Hajós et al 1995) due to an enhanced activation of the somatodendritic 5-HT 1A autoreceptor by an increased level of extracellular 5-HT in the raphe (Adell and Artigas 1991;Bel and Artigas 1993;Hajós et al 1995;Gartside et al 1995;Rutter et al 1995;Béïque et al 1999). ACh-induced firing activity in control and in 5,7-DHT-lesioned rats is shown in B.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations